Modelling trends in contraception usage in Nigeria and Ghana (2018)
This study examines trends in contraception usage using Demographic and Health Survey (DHS) data from Nigeria (2013) and Ghana (2008, 2014). We used a cubic spline to estimate values between intervals, analysed using the time-series neural network model and forecasting till 2030. Results show contraception usage increasing with an average rate of 4.4 per cent, desire not to use declining at an average rate of 0.7 per cent and the use of modern contraception increasing at an average rate of 5.1 per cent. Use of traditional contraception is still increasing in Nigeria at a rate of 0.6 per cent but declining in Ghana at a rate of 0.3 per cent. By 2030, injectables would be mostly used, while the withdrawal method will be preferred among those still in favour of the traditional method. These trends show the readiness of the two countries to embrace the use of modern contraception in an effort to promote the campaign for Planned Parenthood and Family Programme.